Comparison of Computerized Tomography (CT) Scan, Clinical and Para-clinical Findings in Hospitalized Vaccinated and Unvaccinated COVID-19 Patients: A Pilot Study from Babol County - Hesamoddin Arabnozari; Farzin Sadeghi; Mohammadreza Tabatabaie; Ghazaleh Hosseininozari; Mana Baziboron; Masoumeh Bayani (Gazi Medical Journal)
Objective: Vaccination plays a crucial role in preventing severe lung disease and reducing hospitalization rates among patients with coronavirus disease-2019 (COVID-19). In this study, researchers compared lung computed tomography (CT) scans of vaccinated and unvaccinated individuals with COVID-19, along with clinical and para-clinical findings. Methods: This study was conducted at Ayatollah Rouhani Hospital in Babol, Iran, between July and November 2021. The researchers selected 106 confirmed COVID-19 patients and divided them into two groups: 53 fully vaccinated individuals who received the Sinopharm vaccine and 53 unvaccinated individuals. Demographics, laboratory, and imaging data were collected. Results: The mean age of hospitalized patients with COVID-19 was 59.8±16.1 years. The most common CT finding in both groups was bilateral ground glass opacities, observed in 95 patients (89.6%). Significant associations were found between the vaccinated and unvaccinated groups regarding hospital stay duration, oxygen saturation, intensive care unit admission, lactate dehydrogenase levels, and erythrocyte sedimentation rate index. Conclusion: This study revealed no difference in the pattern of pulmonary involvement between vaccinated and unvaccinated individuals with COVID-19, except for the peribronchovascular pattern, which was more commonly observed in unvaccinated patients. Other common patterns of pulmonary involvement were also more prevalent among unvaccinated individuals. These findings emphasize the effectiveness of COVID-19 vaccination, as the vaccinated group had a lower rate of pulmonary involvement. This highlights the need for widespread vaccination to effectively combat COVID-19.